Pendampingan Transformasi Digital UMKM Melalui Strategi SoLoMo Marketing di TikTok: PKM pada Moza Laundry Bandar Lampung - Lis Andriani HR; Tiara Prisca Sabilla; M Ramadhani Sanjaya; Anggia Ayu Handini; Intan Berliana; M. Akbar Fikardo; Miftahhudin Miftahhudin; Pandu Firmansyah (Universitas 45 Surabaya, 2025)
This Community Service Program (PKM) was carried out with the aim of assisting Moza Laundry, an MSME in Bandar Lampung, in its digital transformation process through the application of the SoLoMo Marketing (Social, Local, Mobile) strategy on the TikTok platform. The background of this activity stems from the challenges faced by MSMEs in increasing competitiveness in the digital era, particularly in leveraging short-video-based social media for promotion and customer interaction. The implementation method consisted of several stages: initial observation, training and mentoring, content strategy implementation, as well as monitoring and evaluation. The results show that the application of the SoLoMo strategy helped the partner enhance digital customer interaction, strengthen local identity within content, and optimize the use of mobile formats suited to TikTok user characteristics. In addition, this activity produced outputs such as an active TikTok account with a SoLoMo-based content strategy, a practical module for digital content management, and activity documentation as a means of dissemination. This PKM initiative is expected to provide sustainable benefits for Moza Laundry and serve as a model for the practical implementation of digital content strategies for other service-based MSMEs in facing the challenges of digital transformation.